Perbandingan Kinerja Jaringan Syaraf Tiruan Dan Fuzzy Inference System Untuk Prediksi Prestasi Peserta Didik - Siti Helmiyah; Shofwatul ‘Uyun (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2017)
Achievement is a result of someone who excels in any field. In the educational world, achievement is often associated with academic value that serve as a reference for learners say in academic achievement. Manual data processing takes long time. It is necessary to use the achievements of predictive computing system that can helpful for the prediction process. Data taken from MAN Model Palangkaraya form of eleven subjects of UAS when MTs value and the average value of one semester report cards when the Supreme Court. For the neural network backpropagation data is normalized with small intervals are [0.1, 0.9] and for data fuzzy inference system is the original data is multiplied 10. Then do the testing using neural networks and fuzzy inference system which will compare the results obtained. Based on data have been tested, the percentage of learners' achievements prediction on back propagation neural network in the training and validation process to produce a percentage of 100% with one hidden layer architecture, the optimal parameters MSE = 0.0001, learning rate = 0 , 9, momentum = 0.4. As for the prediction of learners' achievements in the fuzzy inference system mamdani method by using S curve and bell curve (PI curve) to produce a percentage of 83.8%.